From ‘Effortful Use’ to ‘Contextual Improvisation’: Skill Acquisition Theory and Program Planning - Thomas J. Sork (Adult Education Research Conference, 2019)
This paper brings together two bodies of theoretical work—program planning and skill acquisition—to suggest a new way to think about how adult educators become expert program planners.
Keywords: Program planning; skill acquisition; novice to expert; planning theory